1986
DOI: 10.1113/jphysiol.1986.sp015951
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and cardiac output during the onset of exercise, and during voluntary hyperventilation, in humans.

Abstract: SUMMARY1. Three normal subjects performed rest-exercise transitions on a cycle ergometer, from rest to unloaded pedalling (0 W), 50, 100 and 150 W. Each experiment was performed in triplicate, with randomized work load order, in two sessions. Ventilation was obtained breath-to-breath by integration of a pneumotachygraph signal, and cardiac output beat-to-beat by a new development of the Doppler technique. Results were bin-averaged in 4 s bins over the first 20 s, and compared to resting values.2. Both ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
36
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 34 publications
7
36
0
Order By: Relevance
“…However, active hyperventilation has not been shown to have a significant effect on MAP (16), nor does breathing rate or breathing volume change CO (8,15,16,19). Furthermore, it has been reported that HR does not change during short-term hyperventilation (7,19,27). Thus existing evidence does not support that cardiovascular variables are significantly affected by the rebreathing maneuver itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, active hyperventilation has not been shown to have a significant effect on MAP (16), nor does breathing rate or breathing volume change CO (8,15,16,19). Furthermore, it has been reported that HR does not change during short-term hyperventilation (7,19,27). Thus existing evidence does not support that cardiovascular variables are significantly affected by the rebreathing maneuver itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, however, soon identified two components of the V O 2 kinetics: 1) a rapid, almost immediate phase (phase I) (5,54,55), which they attributed to an immediate increase in cardiac output (Q ) at exercise start; and 2) a subsequent slower phase (phase II), to which they restricted the influence of muscle metabolic adjustments. The strongest support to this view came from the demonstration that the kinetics of Q (12,13,16,60) and arterial O 2 flow (Q a O 2 ) (27) are very rapid.…”
mentioning
confidence: 85%
“…It has been shown that short-term hyperventilation has no effect on MAP (14) and HR (6,19,28). The breathing rate and rebreathing volume also have no influence on CO (5,12,14,19).…”
Section: Cardiac Outputmentioning
confidence: 99%